Municipal sludge-based biochar material as well as preparation method and application thereof

The preparation of municipal sludge-based biochar materials through one-step carbonization-activated method has solved the problems of high cost, low mechanical strength, poor chemical stability and poor regeneration ability of existing biochar materials, and achieved efficient and economical adsorption effect of organic dyes, which is in line with environmental protection principles.

CN119746815AActive Publication Date: 2025-04-04JIANGSU UNIV +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411946929.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

Existing biochar materials have high cost, low mechanical strength, poor chemical stability and poor regeneration capabilities, making it difficult to effectively play a role in practical applications.

Method used

The one-step carbonization-activated method is used to heat-treat the mixture of municipal sludge and organic solid waste, and mixed steam of sodium hydroxide steam and water vapor is introduced to prepare municipal sludge-based biochar material with high specific surface area and good cyclic adsorption properties.

Benefits of technology

The prepared municipal sludge-based biochar material has a high specific surface area, good cyclic adsorption performance and efficient organic dye removal rate. It is also low in cost and simple in preparation process, which is in line with the principle of "waste control" that is in line with environmental protection concepts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119746815A_ABST
    Figure CN119746815A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biochar material preparation, and discloses a municipal sludge-based biochar material as well as a preparation method and application thereof. The preparation method comprises the following steps: mixing municipal sludge and organic solid waste, and drying to obtain a mixture; the obtained mixture is heated to a heat treatment temperature, mixed steam is introduced at the heat treatment temperature for a reaction, then cooling and drying are conducted in sequence, and a biochar material is obtained; the mixed steam is mixed steam of sodium hydroxide steam and water vapor. The municipal sludge-based biochar has a high specific surface area (120-300 m < 2 > / g) and can circularly adsorb organic dye, and the removal rate of the organic dye by the biochar material after multiple cycles can still be maintained at 90% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biochar material preparation, and in particular to a municipal sludge-based biochar material and a preparation method and application thereof. Background Art

[0002] At present, the materials used for organic dye adsorption in daily life include activated carbon, diatomaceous earth, chitosan, resin and cellulose. Among them, activated carbon is a very common adsorption material with high specific surface area and rich pore structure, which can effectively adsorb organic dyes. However, the production cost of activated carbon is high, and after adsorbing dyes, the regeneration process of activated carbon is relatively complicated and time-consuming, which affects its long-term use efficiency. Diatomaceous earth is a natural material with a porous structure and can adsorb organic dyes, but the adsorption capacity of diatomaceous earth is relatively low, and a large amount of use is required to achieve the ideal adsorption effect, and the mechanical strength of diatomaceous earth is not enough to withstand the pressure in practical applications. Chitosan is a natural polymer material with good biocompatibility and adsorption performance, but chitosan is easily dissolved under acidic conditions, which limits its application in acidic environments. This chitosan is mainly derived from crustaceans, and its source is limited by season and region. Resin is a synthetic material with high adsorption performance and is often used in water treatment and dye recovery, but the use conditions of resin are relatively harsh, and its chemical stability is affected by specific environmental conditions. Cellulose is a natural polymer material with good adsorption properties. It is often used in wastewater treatment and dye adsorption. In order to improve the adsorption performance, cellulose may need to be chemically modified, which increases the production cost and complexity of preparation. The adsorption properties of cellulose are better for some dyes, but not for others.

[0003] In addition, there are some new materials, such as metal-organic framework nanomaterials (MOFs), Keggin-type polyacid-based nanomaterials, MXene nanomaterials, etc., which are used for the efficient adsorption of organic dyes. However, due to the biological toxicity, high preparation cost and extremely low yield of the materials, they cannot play an effective role in actual engineering.

[0004] Therefore, it is of great significance to study and obtain a municipal sludge-based biochar material with excellent adsorption performance, no biological toxicity and renewability, as well as a preparation method with low production cost, simple preparation process and high yield. Summary of the invention

[0005] In view of this, the present invention provides a municipal sludge-based biochar material and a preparation method and application thereof, the purpose of which is to solve the problems of high cost, low mechanical strength, poor chemical stability and poor regeneration ability of biochar materials in the prior art.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] The present invention provides a method for preparing a municipal sludge-based biochar material, comprising the following steps:

[0008] 1) mixing municipal sludge and organic solid waste and drying them to obtain a mixture;

[0009] 2) heating the obtained mixture to a heat treatment temperature, introducing mixed steam at the heat treatment temperature to react, and then cooling and drying in sequence to obtain a biochar material;

[0010] The mixed steam is a mixed steam of sodium hydroxide steam and water vapor.

[0011] Preferably, in step 1), the organic solid waste includes one or more of plant straw, livestock and poultry manure and food waste.

[0012] Preferably, in the step 1), the mass ratio of municipal sludge to organic solid waste is 2 to 7:1; the drying temperature is 40 to 80° C., and the drying time is 20 to 25 hours.

[0013] Preferably, in step 2), an inert gas is introduced during the process of heating to the heat treatment temperature, introducing the mixed steam and cooling, and the inert gas is nitrogen with a flow rate of 50 to 200 mL / min.

[0014] Preferably, in step 2), the heating rate to the heat treatment temperature is 2-10°C / min, the heat treatment temperature is 600-900°C; the heat treatment time is 10-120min, and the flow rate of the mixed steam is 10-1000mL / min.

[0015] Preferably, in step 2), the cooling temperature is 20-30° C.; the drying temperature is 30-60° C., and the drying time is 20-26 hours.

[0016] Preferably, the usage ratio of the sodium hydroxide vapor to the water vapor is 0.1 to 1 mol:1L.

[0017] The present invention also provides a municipal sludge-based biochar material prepared by the method for preparing the municipal sludge-based biochar material.

[0018] The present invention also provides the use of the municipal sludge-based biochar material in the adsorption of organic dyes.

[0019] It can be seen from the above technical solutions that, compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention prepares a renewable municipal sludge-based biochar material for organic dye adsorption by using a one-step carbonization-activation method. The prepared biochar material can sustainably adsorb and remove organic dyes. At the same time, organic solid waste such as municipal sludge is used as a preparation raw material, which is in line with the environmental protection concept of "treating waste with waste".

[0021] The municipal sludge-based biochar obtained by the present invention has a high specific surface area (120-300m 2 / g), and can cyclically adsorb organic dyes, and the removal rate of organic dyes by biochar materials after multiple cycles can still be maintained at more than 90%. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.

[0023] Figure 1 This is a scanning electron microscope image of the biochar material obtained in Example 1;

[0024] Figure 2 This is a scanning electron microscope image of the biochar material obtained in Example 2;

[0025] Figure 3 This is a scanning electron microscope image of the biochar material obtained in Example 3;

[0026] Figure 4 This is the Fourier infrared spectrum of the biochar material obtained in Example 1;

[0027] Figure 5 The Fourier infrared spectra of the biochar materials obtained in Example 2 and Comparative Example 1;

[0028] Figure 6 The Fourier infrared spectra of the biochar materials obtained in Example 3 and Comparative Example 2;

[0029] Figure 7 This is the Raman spectrum of the biochar material obtained in Example 1;

[0030] Figure 8 The Raman spectra of the biochar materials obtained in Example 2 and Comparative Example 1;

[0031] Fig. 9 The Raman spectra of the biochar materials obtained in Example 3 and Comparative Example 2;

[0032] Fig.10This is the cyclic adsorption diagram of the biochar material obtained in Example 1;

[0033] Fig.11 The cyclic adsorption diagram of the biochar material obtained in Example 2 and Comparative Example 1;

[0034] Fig.12 This is the cyclic adsorption diagram of the biochar material obtained in Example 3 and Comparative Example 2. DETAILED DESCRIPTION

[0035] The present invention provides a method for preparing a municipal sludge-based biochar material, comprising the following steps:

[0036] 1) mixing municipal sludge and organic solid waste and drying them to obtain a mixture;

[0037] 2) heating the obtained mixture to a heat treatment temperature, introducing mixed steam at the heat treatment temperature to react, and then cooling and drying in sequence to obtain a biochar material;

[0038] The mixed steam is a mixed steam of sodium hydroxide steam and water vapor.

[0039] In the present invention, in step 1), the organic solid waste preferably includes one or more of plant straw, livestock and poultry manure and food waste.

[0040] In the present invention, in the step 1), the mass ratio of municipal sludge to organic solid waste is preferably 2-7:1, more preferably 3-6:1, and more preferably 4-5:1; the drying temperature is preferably 40-80°C, more preferably 50-70°C, and more preferably 60-65°C; the drying time is preferably 20-25h, more preferably 21-24h, and more preferably 22-23h.

[0041] In the present invention, in the step 2), an inert gas is introduced during the process of heating to the heat treatment temperature, introducing the mixed steam and cooling. The inert gas is preferably nitrogen, and the flow rate of the inert gas is preferably 50 to 200 mL / min, more preferably 80 to 150 mL / min, and more preferably 100 to 120 mL / min.

[0042] In the present invention, in the step 2), the heating rate to the heat treatment temperature is preferably 2-10°C / min, more preferably 4-8°C / min, more preferably 5-6°C / min, the heat treatment temperature is preferably 600-900°C, more preferably 650-850°C, more preferably 700-800°C; the heat treatment time is preferably 10-120min, more preferably 40-90min, more preferably 60-80min, and the flow rate of the mixed steam is preferably 10-1000mL / min, more preferably 100-800mL / min, more preferably 300-500mL / min.

[0043] In the present invention, in the step 2), the cooling temperature is preferably 20-30°C, more preferably 22-28°C, and more preferably 24-26°C; the drying temperature is preferably 30-60°C, more preferably 35-55°C, and more preferably 40-50°C; the drying time is preferably 20-26h, more preferably 21-25h, and more preferably 22-24h.

[0044] In the present invention, washing is performed after cooling, the washing agent is preferably water, and the number of washing times is preferably 5 to 10 times, more preferably 6 to 9 times, and even more preferably 7 to 8 times.

[0045] In the present invention, the usage ratio of the sodium hydroxide vapor to the water vapor is preferably 0.1-1 mol:1L, more preferably 0.3-0.8 mol:1L, and more preferably 0.5-0.6 mol:1L.

[0046] The present invention also provides a municipal sludge-based biochar material prepared by the method for preparing the municipal sludge-based biochar material.

[0047] The present invention also provides the use of the municipal sludge-based biochar material in the adsorption of organic dyes.

[0048] In the present invention, the biochar material can be regenerated after the organic dye is adsorbed, and the regeneration step is: heat-treating the biochar material after the organic dye is adsorbed and then cooling it to obtain a regenerated biochar material;

[0049] During the heat treatment, an inert gas is introduced, and the inert gas is preferably nitrogen. The flow rate of the inert gas is preferably 50-200 mL / min, more preferably 80-150 mL / min, and more preferably 100-120 mL / min. The heating rate of the heat treatment is preferably 2-10°C / min, more preferably 4-8°C / min, and more preferably 5-6°C / min. The heat treatment temperature is preferably 300-500°C, more preferably 350-450°C, and more preferably 400-420°C. The heat treatment time is preferably 0.5-2h, and more preferably 1-1.5h. The cooling temperature is preferably 20-30°C, more preferably 22-28°C, and more preferably 24-26°C.

[0050] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0051] In the embodiments and comparative examples of the present invention, municipal sludge comes from a thickening tank of a municipal sewage treatment plant, and the water treatment process used in the municipal sewage treatment plant is an anaerobic-anoxic-aerobic process. Before the municipal sludge enters the thickening tank, polyacrylamide flocculant needs to be added.

[0052] Example 1

[0053] Municipal sludge and wheat straw were mixed in a mass ratio of 2:1 and dried at 60°C for 24h to obtain a mixture;

[0054] The mixture was placed in a high-temperature tube furnace, and the temperature was raised to 800°C at a rate of 5°C / min in an environment where nitrogen (flow rate was 100mL / min) was continuously introduced. Then, at 800°C, a mixed vapor of sodium hydroxide vapor and water vapor was continuously introduced into the high-temperature tube furnace through a water vapor generator at a rate of 100mL / min for 1h (nitrogen was still introduced at a flow rate of 100mL / min in this process, and the ratio of sodium hydroxide vapor to water vapor was 0.1mol:1L). After the introduction of the mixed vapor of sodium hydroxide vapor and water vapor was completed, the nitrogen was still introduced, and the mixture was naturally cooled to 25°C. The cooled product was washed with water 8 times, and then dried at 55°C for 24h to obtain the biochar material.

[0055] Example 2

[0056] The municipal sludge and rice husk were mixed in a mass ratio of 3:1 and dried at 80°C for 24h to obtain a mixture;

[0057] The mixture was placed in a high-temperature tube furnace, and the temperature was raised to 850°C at a rate of 10°C / min in an environment where nitrogen (flow rate was 150 mL / min) was continuously introduced. Then, at 850°C, a mixed vapor of sodium hydroxide vapor and water vapor was continuously introduced into the high-temperature tube furnace at a rate of 1000 mL / min for 1.5 h through a water vapor generator (nitrogen was still introduced at a flow rate of 150 mL / min in this process, and the amount ratio of sodium hydroxide vapor to water vapor was 1 mol: 1 L). After the introduction of the mixed vapor of sodium hydroxide vapor and water vapor was completed, the nitrogen was still introduced, and the mixture was naturally cooled to 25°C. The cooled product was washed with water 5 times, and then dried at 60°C for 24 h to obtain the biochar material.

[0058] Example 3

[0059] Municipal sludge and cow dung were mixed in a mass ratio of 2:1 and dried at 60°C for 24h to obtain a mixture;

[0060] The mixture was placed in a high-temperature tube furnace, and the temperature was raised to 600°C at a heating rate of 5°C / min in an environment where nitrogen (flow rate of 50 mL / min) was continuously introduced. Then, at 600°C, a mixed vapor of sodium hydroxide vapor and water vapor was continuously introduced into the high-temperature tube furnace through a water vapor generator at a rate of 500 mL / min for 1 h (nitrogen was still introduced at a flow rate of 50 mL / min in this process, and the ratio of sodium hydroxide vapor to water vapor was 0.5 mol: 1 L). After the introduction of the mixed vapor of sodium hydroxide vapor and water vapor was completed, the nitrogen was still introduced, and the mixture was naturally cooled to 25°C. The cooled product was washed with water 5 times, and then dried at 60°C for 24 h to obtain the biochar material.

[0061] Comparative Example 1

[0062] The municipal sludge and rice husk were mixed in a mass ratio of 3:1 and dried at 80°C for 24h to obtain a mixture;

[0063] The mixture was placed in a high-temperature tube furnace, and the temperature was raised to 850°C at a heating rate of 10°C / min in an environment where nitrogen (flow rate was 150 mL / min) was continuously introduced. Then, water vapor was continuously introduced into the high-temperature tube furnace at a rate of 1000 mL / min for 1.5 h at 850°C through a water vapor generator (nitrogen was still introduced at a flow rate of 150 mL / min during this process). After the introduction of steam was completed, the nitrogen was still introduced, and the mixture was naturally cooled to 25°C to obtain a primary biochar material.

[0064] The primary biochar material was mixed with 1M sodium hydroxide solution in a dosage ratio of 1g:10mL, stirred at 400rpm for 4h, and then dried at 80℃ for 24h. Then, it was placed in a high-temperature tube furnace again, and heated to 850℃ at a rate of 10℃ / min in an environment with continuous nitrogen flow (flow rate of 150mL / min), and kept warm for 1h. Then, it was naturally cooled to 25℃ in an environment with nitrogen flow, and the cooled product was washed with water 8 times, and then dried at 80℃ for 24h to obtain the biochar material.

[0065] Comparative Example 2

[0066] Municipal sludge and cow dung were mixed in a mass ratio of 2:1 and dried at 60°C for 24h to obtain a mixture;

[0067] The mixture was placed in a high-temperature tube furnace, and the temperature was raised to 600°C at a rate of 5°C / min in an environment where nitrogen (flow rate was 50 mL / min) was continuously introduced. Then, water vapor was continuously introduced into the high-temperature tube furnace at a rate of 500 mL / min for 1 h at 600°C through a water vapor generator (nitrogen was still introduced at a flow rate of 50 mL / min during this process). After the introduction of steam was completed, the nitrogen was still introduced, and the mixture was naturally cooled to 25°C to obtain a primary biochar material.

[0068] The primary biochar material was mixed with 0.5M sodium hydroxide solution in a dosage ratio of 1g:20mL, stirred at 600rpm for 4h, and then dried at 60℃ for 24h. Then, it was placed in a high-temperature tube furnace again, and heated to 600℃ at a rate of 5℃ / min in an environment with continuous nitrogen flow (flow rate of 50mL / min), and kept warm for 1h. Then, it was naturally cooled to 25℃ in an environment with nitrogen flow, and the cooled product was washed with water 8 times, and then dried at 60℃ for 24h to obtain the biochar material.

[0069] The biochar materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 were respectively tested for the cyclic adsorption performance of organic dyes, where the organic dyes may be rhodamine B or methylene blue:

[0070] The specific detection experimental steps are as follows:

[0071] Isothermal adsorption experiment: 1L of organic dye aqueous solution of different concentrations (40mg / L, 80mg / L, 100mg / L, 250mg / L, 500mg / L, 700mg / L and 1000mg / L) was added to 1g of biochar material. After sufficient adsorption for 24h under magnetic stirring, the upper layer of solution was taken to measure and calculate the adsorption amount.

[0072] Adsorption kinetics experiment: 1 g of biochar material was added to 1 L of organic dye aqueous solution (100 mg / L). With the assistance of magnetic stirring, the upper layer of solution was taken in turn at different time periods (0 min, 20 min, 40 min, 60 min, 90 min, 120 min, 180 min, 240 min and 300 min) to measure and calculate the adsorption amount.

[0073] Adsorption thermodynamics experiment: 1g of biochar material was added to 1L of organic dye aqueous solution (100mg / L), and the adsorption environment temperature of the material was maintained at a specific value (293K, 303K and 313K) by a constant temperature water bath. After fully adsorbing for 24h under magnetic stirring, the upper layer solution was taken to measure and calculate the adsorption amount.

[0074] The adsorbed biochar material was placed in a high-temperature tubular furnace and heated to 300°C at a rate of 5°C / min in an environment where nitrogen was continuously introduced (flow rate was 100 mL / min), and maintained in this environment for 0.5 h. It was then naturally cooled to 25°C, completing the recovery of the biochar material.

[0075] The above operation was repeated three times for the biochar materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2, respectively, and the adsorption amount and adsorption removal rate of the biochar materials were recorded.

[0076] The scanning electron microscope image of the biochar material obtained in Example 1 is as follows Figure 1 As shown. Figure 1 It can be seen that after mixed pyrolysis, straw and municipal sludge formed a tight "cutting" structure, which made the strip-like channels in the straw biochar and the channels in the municipal sludge biochar interconnected, changing the pore structure of the single-component biochar.

[0077] The scanning electron microscope image of the biochar material obtained in Example 2 is as follows Figure 2 As shown. Figure 2 It can be seen that after the joint activation of alkali and steam, a large number of pores appeared on the surface of biochar, indicating that the internal part of the material was effectively connected with the external environment, and the municipal sludge and rice husk were fused and rearranged under the action of heat treatment to become a whole, which further supplemented the original municipal sludge pore structure and was beneficial to the improvement of related adsorption performance.

[0078] The scanning electron microscope image of the biochar material obtained in Example 3 is as follows Figure 3 As shown. Figure 3 It can be seen that since cow dung itself does not have significant regularity in its microstructure, the product obtained by carbonizing and activating it with municipal sludge has a block-like microstructure. After being activated by alkali and water, the microscopic surface of the material becomes uneven, which provides a large number of active sites for the adsorption of organic dyes.

[0079] The Fourier infrared spectrum of the biochar material obtained in Example 1 is as follows Figure 4 As shown. Figure 4 It can be seen that the absorption peak caused by -OH stretching vibration appears at 3432 cm -1 Its change is used to judge the contribution of hydrogen bonding in the adsorption process. -1 and 2975cm -1 The absorption peak is caused by the stretching vibration of C and H functional groups, which are common functional groups in biochar. -1 The absorption peak of CO functional group stretching vibration appears at 1045 cm -1 Accompanied by a small amount of stretching vibration of Si-O functional groups. CO mainly comes from cellulose, hemicellulose and lignin. 400~800cm -1 A series of absorption peaks appeared in the range, which was attributed to the bending vibration of Si-O and the bending vibration of Si-O-Si bridging oxygen.

[0080] The Fourier infrared spectra of the biochar materials obtained in Example 2 and Comparative Example 1 are as follows: Figure 5 As shown. Figure 5 It can be seen that the biochar material obtained in Example 2 has a red shift in the spectrum compared to the biochar material obtained in Comparative Example 1. This phenomenon shows that the one-step method shown in Example 2 and the two-step method shown in Comparative Example 1 have a significant effect on the functional groups of the final product and can effectively change the electron transfer mode. The change in the electron transfer mode is conducive to the improvement of the material's adsorption capacity for organic dyes.

[0081] The Fourier infrared spectra of the biochar materials obtained in Example 3 and Comparative Example 2 are shown in Figure 6 As shown. Figure 6 It can be seen that the transmittance of -CH2 and -CH3 in the biochar material obtained in Example 3 is significantly enhanced, which indicates that the content and intensity of the carbon component in the biochar material obtained by the one-step method shown in Example 3 are higher than those of the biochar material obtained by the two-step method shown in Comparative Example 2. The same signal enhancement phenomenon also occurs in CO and Si-O, proving that there are more adsorption active sites in the biochar material prepared by the one-step method, which is beneficial to improving the adsorption performance of the material for organic dyes.

[0082] The Raman spectrum of the biochar material obtained in Example 1 is as follows Figure 7 As shown. Figure 7 Visible, located at about 1580cm -1 The G peak of graphite and the E 2gVibration mode related, that is, sp 2 The G peak is the stretching vibration of hybrid carbon atoms in the graphite plane, so it is also an important indicator for evaluating the degree of graphitization of biochar. -1 The D peak at 1 is related to the defects, disordered structure or sp 3 The intensity ratio of D peak to G peak (I D / I G ) is usually used to describe the graphitization and defect degree of biochar. After calculation, I D / I G The value is 0.89, which is a low I D / I G The value indicates that the graphitization process in biochar is significant and the biochar has more sp 2 Hybridized carbon atoms and relatively complete graphite layer structure.

[0083] The Raman spectra of the biochar materials obtained in Example 2 and Comparative Example 1 are as follows: Figure 8 As shown. Figure 8 It can be seen that compared with the biochar material obtained by the two-step method shown in Comparative Example 1, the biochar material obtained by the one-step method shown in Example 2 has a stronger Raman signal, especially in the range of 2500-3000 cm -1 The presence of the 2D peak indicates that there is an obvious layered graphite structure in the biochar material. In the adsorption experiment, the presence of this structure can ensure the maximum contact between the biochar and the organic dye. In addition, the spectrum noise of the biochar material obtained in Example 2 is lower than that of the biochar material obtained in Comparative Example 1, indicating that the impurity content in the biochar material obtained in Example 2 is lower, and the biochar has a higher content and degree of graphitization.

[0084] The Raman spectra of the biochar materials obtained in Example 3 and Comparative Example 2 are as follows: Fig. 9 As shown. Fig. 9 It can be seen that the signals of the biochar material obtained by the one-step method shown in Example 3 at the G peak and the D peak are higher than those of the biochar material obtained by the two-step method shown in Comparative Example 2, indicating that the internal structure of the biochar material obtained in Example 3 is more complete, while there are more defects on the surface, which indicates that the pore adsorption and active site adsorption jointly improve the adsorption capacity of the material. In addition, the lower Raman shift (0-800cm -1 ), the biochar material obtained in Example 3 has a more regular Si-O bond signal, while the biochar material obtained in Comparative Example 2 has other spur peaks, indicating that the latter contains more inorganic impurities.

[0085] The cyclic adsorption diagram of the biochar material obtained in Example 1 is as follows Fig.10 As shown. Fig.10It can be seen that cyclic adsorption is an important indicator to measure the adsorption capacity and cyclic capacity of biochar. After three rounds of adsorption experiments, the biochar material still maintains a high adsorption removal rate (over 90%) for methylene blue, and its adsorption amount is about 45 mg / g. The activation process not only improves the pore structure of biochar, but also the internally generated SiO2 can effectively increase the biochar's resistance to thermal shock and reduce the functional loss caused by cyclic regeneration. In addition, when biochar was initially prepared, the addition and activation of organic solid waste jointly introduced a large number of active sites and surface functional groups to the biochar. Although some active sites lost their activity and the functional groups changed in type during the cyclic regeneration process, the remaining original active sites and functional groups still kept the adsorption performance of biochar at a high level and stability.

[0086] The cyclic adsorption diagrams of the biochar materials obtained in Example 2 and Comparative Example 1 are shown in Fig.11 As shown. Fig.11 It can be seen that the three adsorption removal rates of methylene blue by the biochar material obtained in Example 2 are 97.75%, 94.24% and 92.11% respectively; while the three adsorption removal rates of methylene blue by the biochar material obtained in Comparative Example 1 are 90.31%, 85.21% and 83.19% respectively. By comparison, it was found that in the same batch of adsorption experiments, the adsorption removal rate of methylene blue by the biochar material obtained in Example 2 was higher than that of the biochar material obtained in Comparative Example 1. In addition, after three adsorption experiments, the adsorption removal of methylene blue by the biochar material obtained in Example 2 remained above 90%, while the adsorption removal rate of methylene blue by the biochar material obtained in Comparative Example 1 was close to 80%. Therefore, it can be seen that although the biochar material obtained in Comparative Example 1 showed an excellent and stable adsorption removal rate for methylene blue, the adsorption performance of the biochar material obtained in Example 2 was even better.

[0087] The cyclic adsorption diagrams of the biochar materials obtained in Example 3 and Comparative Example 2 are shown in FIG. Fig.12 As shown. Fig.12 It can be seen that the three adsorption removal rates of the biochar material obtained in Example 3 are 97.58%, 93.13% and 90.95%, respectively, while the three adsorption removal rates of the biochar material obtained in Comparative Example 2 are 91.37%, 87.83% and 82.14%, respectively. In any adsorption removal experiment of Rhodamine B, the removal effect of the biochar material obtained in Example 3 is always better than that of the biochar material obtained in Comparative Example 2. With the increase in the number of adsorption experiments, the adsorption removal rate of Rhodamine B by the biochar material obtained in Example 3 decreased by 6.79%, while the adsorption removal rate of Rhodamine B by the biochar material obtained in Comparative Example 2 decreased by 9.68%. It can be seen that the adsorption removal effect of Rhodamine B by the biochar material obtained in Example 3 is better than that of the biochar material obtained in Comparative Example 2.

[0088] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing municipal sludge-based biochar material, characterized in that: The steps include: 1) mixing municipal sludge and organic solid waste and drying them to obtain a mixture; 2) heating the obtained mixture to a heat treatment temperature, introducing mixed steam at the heat treatment temperature to react, and then cooling and drying in sequence to obtain a biochar material; The mixed steam is a mixed steam of sodium hydroxide steam and water vapor.

2. The method for preparing a municipal sludge-based biochar material according to claim 1, characterized in that: In the step 1), the organic solid waste includes one or more of plant straw, livestock and poultry manure and food waste.

3. The method for preparing a municipal sludge-based biochar material according to claim 2, characterized in that: In the step 1), the mass ratio of municipal sludge to organic solid waste is 2-7:1; the drying temperature is 40-80° C., and the drying time is 20-25 hours.

4. The method for preparing a municipal sludge-based biochar material according to claim 3, characterized in that: In the step 2), an inert gas is introduced during the process of heating to the heat treatment temperature, introducing the mixed steam and cooling. The inert gas is nitrogen and the flow rate of the inert gas is 50 to 200 mL / min.

5. The method for preparing a municipal sludge-based biochar material according to claim 4, characterized in that: In the step 2), the heating rate to the heat treatment temperature is 2-10°C / min, the heat treatment temperature is 600-900°C; the heat treatment time is 10-120min, and the flow rate of the mixed steam is 10-1000mL / min.

6. The method for preparing a municipal sludge-based biochar material according to claim 4 or 5, characterized in that: In the step 2), the cooling temperature is 20-30° C.; the drying temperature is 30-60° C., and the drying time is 20-26 hours.

7. The method for preparing a municipal sludge-based biochar material according to claim 6, characterized in that: The dosage ratio of the sodium hydroxide vapor to the water vapor is 0.1-1 mol:1L.

8. The municipal sludge-based biochar material obtained by the method for preparing a municipal sludge-based biochar material according to any one of claims 1 to 7.

9. Use of the municipal sludge-based biochar material according to claim 8 in the adsorption of organic dyes.

Citation Information

Patent Citations

  • Thermal timber modification method

    CN108687905A

  • Oil stain adsorbent and preparation method thereof

    CN113318709A

  • Super-oleophylic water purification composite adsorbent

    CN116474722A

  • Apparatus for determining fault of vehicle air conditioning system and method thereof

    KR1020220148410A

  • Materials and methods for production of activated carbons

    US20140162873A1